Design of Dipalmitoyl Lecithin Liposomes Loaded with Quercetin and Rutin and Their Release Kinetics from Carboxymethyl Cellulose Edible Films - Osorio-Lira, F; Silva-Weiss, A; Silva-Vera, W; Gimenez-Castillo, B (Elsevier Ltd, 2018)
Quercetin and rutin were encapsulated in liposomes based on dipalmitoyl lecithin. The effect of liposomal formulation stage for flavonol incorporation and the size-reducing method on encapsulation efficiency (EE) of flavonols and physical properties of liposomes were evaluated. In addition, the release mechanism and kinetics of polyphenols from carboxymethyl cellulose edible films were studied through modeling and simulation equations. When flavonols were incorporated during the phospholipid film formation stage, low polydispersity index (0.32 and 0.20) and high EE (88.9 and 74.1%) of quercetin and rutin, respectively, were obtained. Sonication gave liposomes with higher zeta potential (36.9–42.4 mV) than extrusion (13.3–17.1 mV), and quercetin-loaded liposomes were the most stable during 21 days of storage. In CMC films, diffusion coefficients of flavonols were higher for non-encapsulated flavonols than encapsulated flavonols. The release of non-encapsulated quercetin and rutin from CMC films was 25% and 24% higher than in the case of encapsulated quercetin and rutin at day 21. The released mechanism agreed with Fickian diffusion for encapsulated and non-encapsulated quercetin, whereas the release mechanism of encapsulated and non-encapsulated rutin agreed with non-Fickian diffusion. These results highlight the relevance of using liposomes as encapsulation technology, able to preserve polyphenols and control their release in the design of edible films with antioxidant activity for improving food shelf life. © 2018 Elsevier Ltd